Wujhāt Naẓar Dārisī al-Lughah al-ʿArabiyyah Naḥwa Taʿallum Māddat al-Naḥw al-ʿArabī - Hanan Mustafa (Lisanudhad: Jurnal Bahasa, Pembelajaran dan Sastra Arab, 2016)
Arabic grammar constitutes one of the most fundamental disciplines in linguistic studies, particularly in preserving the accuracy and integrity of the Arabic language against linguistic errors and dialectal influences. As Arabic continues to be used globally in various educational, religious, and communicative contexts, grammar instruction remains an essential component of Arabic language education. This study aims to explore the perspectives of non-native university students of Arabic regarding the learning of Arabic grammar as a formal academic subject. Employing a qualitative research approach, data were collected and analyzed through focus group interviews involving two male and three female students from different academic levels. The findings reveal that participants encountered various linguistic and non-linguistic challenges in learning Arabic grammar. Despite these difficulties, they expressed a positive attitude toward grammar learning and reported that it appeared relatively easy during the initial stages of study. The study suggests that teachers should utilize students’ perspectives to improve grammar teaching methods and enhance learners’ linguistic competence and classroom performance. Furthermore, the article provides practical recommendations for classroom instruction based on the experiences and perceptions of Arabic language learners.